Successful Surgical Treatment of a Recurrent Esophageal Malignant Gastrointestinal Neuroectodermal Tumor - Song, Seung Hwan (Korean J Thorac Cardiovasc Surg, 2018)
Malignant gastrointestinal neuroectodermal tumor (GNET) is a very rare disease entity, especially in the esophagus. The diagnosis of GNET is based on histologic, immunohistochemical, and genetic findings. The choice of treatment is complete resection, and further treatment options can be considered. Herein, we describe a case of successful surgical treatment of a 23-year-old man with recurrent malignant esophageal GNET.